The Effect of Competition Effort on Vital Capacity Level on Young Soccer Players Aged (14 – 16) Years old - Abdulhameed, Firas; Abdulkareem, Hateem (Journal of Physical Education, 2021)
The importance of the research lies in studying the direct effect of competition effort on the level of vital capacity level in young soccer players since it is one of the important physiological indicators that the coach should monitor. The problem of the research lies in identifying the direct effect of vital capacity in young soccer players. The research aimed at identifying the effect of competition effort on vital capacity in young soccer players. The researchers hypothesized the effect of competition effort on a vital capacity level in soccer players and differences between pre and post-tests in the subjects of the research. The researchers used the deceptive method on (62) young soccer players to conclude that competition effort has a great effect on the vital capacity of young soccer players. Finally, they recommended young soccer players as well as making studies to identify competition effort on other organs and other age groups. In addition to that, the researchers recommended making studies on other team sports on other respiratory system variables in young players as well as other age groups.